T-piece versus self-inflating bag ventilation in preterm neonates at birth - Guinsburg, Ruth; Branco de Almeida, Maria Fernanda; Castro, Junia Sampel de; Goncalves-Ferri, Walusa Assad; Marques, Patricia Franco; Siqueira Caldas, Jamil Pedro; Jornada Krebs, Vera Lucia; Suppo de Souza Rugolo, Ligia Maria [UNESP]; Carvalho Leme de Almeida, Joao Henrique; Luz, Jorge Hecker; Procianoy, Renato S.; Muniz Bandeira Duarte, Jose Luiz; et al. (Bmj Publishing Group, 2018)
Objective To verify whether the use of the T-piece resuscitator compared with the self-inflating bag in preterm infants ventilated at birth modifies survival to hospital discharge without major morbidities. Design Pragmatic prospective cohort study. Setting 20 Brazilian university hospitals of Brazilian Network on Neonatal Research. Patients were 1962 inborn infants in 2014-2015 ventilated at birth with 23-33' weeks gestation and birth weight 400-1499 g without malformations. Patients transferred until the 27th day after birth were excluded. Interventions Positive pressure ventilation at birth with T-piece resuscitator or self-inflating bag without positive end expiratory pressure valve. Intervention with ventilation followed the Brazilian Society of Pediatrics guidelines. The choice of the equipment was at the neonatologist's discretion in each delivery. The main outcome measures were survival to hospital discharge without bronchopulmonary dysplasia, severe peri-intraventricular haemorrhage and periventricular leucomalada. Logistic regression adjusted for confounding variables was applied for main outcome. Results 1456 (74%) were only ventilated with T-piece resuscitator and 506 (26%) with the self-inflating bag. The characteristics of those ventilated with T-Piece resuscitator versus self-inflating bag were birth weight 969 +/- 277 vs 941 +/- 279 g, gestational age 28.2 +/- 2.5 vs 27.8 +/- 2.7 weeks and survival to hospital discharge without major morbidities 47% vs 35%, Logistic regression adjusted for maternal characteristics, obstetric and neonatal morbidities showed that the T-piece resuscitator increased the chance of survival to hospital discharge without major morbidities (OR=1.38; 95% Cl 1.06 to 1.80; Hosmer-Lemeshow goodness of fit: 0.695). Conclusion This study is the first that highlights the effectiveness of T-piece resuscitator ventilation in improving relevant outcomes in preterm neonates.